The effects of supplementing Acacia mearnsii tannin extract on dairy cow dry matter intake, milk production, and methane emission in a tropical pasture - Alves T.P.* (2017)
© 2017, Springer Science+Business Media B.V.The study assessed the effect of Acacia mearnsii tannin extract supplementation grazing dairy cows on dry matter (DM) intake, enteric methane (CH4) emission, and performance. Twelve Holstein cows were divided into two groups and subjected to two treatments that consisted of millet pasture (Pennisetum glaucum L.) plus supplementation with 6 kg of concentrate (750-g/kg ground corn and 250-g/kg soybean meal) including or excluding 120-g tannin extract. The trial design was a double reversal using three periods of 28 days each, with 21 days for the adaption period, and 7 days for sample collection. Herbage intake was measured using the n-alkane technique, and daily CH4 emission was measured with the sulfur hexafluoride tracer gas technique. Individual total DM intake (mean = 17.1 kg/day), herbage DM intake (mean = 11.8 kg/day), and milk production (mean = 19.2 kg/day) were similar between treatments. CH4 emission significantly decreased (32%, P < 0.05) in the animals supplemented with tannin extract, compared to non-supplemented animals. On the other hand, as proportion of DM intake or milk production, methane emission tended to decrease in tannin-supplemented animals. Supplementing dairy cows grazing a millet pasture with 120-g tannin extract reduced daily CH4 emission without affecting animal performance.